Linking farmers to markets: opportunities and challenges for cassava farmers in Malawi - Mahungu, N.M.; Jumbo, S.; Sandifolo, V.S.; Howard, D.; Mhone, A.; Nthonyiwa, A.; Rusike, Joseph (International Institute of Tropical Agriculture, 2010)
In an effort to improve rural farmer’s livelihood, many initiatives have been initiated in Sub-Saharan Africa (SSA) to link cassava farmers to markets. Several models have been used including use of leading entrepreneurs, targeting farmers’ associations/groups, conducting industrial tests to sensitize and create new markets, use of out-growers scheme and use of farmer-to –trader linkages. These models have been applied for a range of value chains in the cassava industry including starch, high quality fermented and non fermented flour, chips and raw cassava roots. Cassava offers the biggest opportunities to uplift livelihoods of resource poor farmers as production has increased and markets for both processed and raw cassava have manifested in recent years. The major challenge has been fostering appropriate linkages between farmers and markets and to transform the increased production to usable products. Lessons from work done in Malawi indicate that use of individual lead entrepreneurs and involvement of private sector partners is key to sustainability of the cassava business. The major motivation for sustainability of the business is ownership and profits generated from the enterprise. Industrial testing of products and training of lead entrepreneurs on appropriate processing technologies are key to create awareness and open new markets. Problems associated with low educational levels, group dynamics, lack of ownership and lack of common vision have been found to be the major limiting factors for group or association owned initiatives.